Effects of feeding corn silage inoculated with microbial additives on the ruminal fermentation, microbial protein yield, and growth performance of lambs - Basso, F. C. [UNESP]; Adesogan, A. T.; Lara, E. C. [UNESP]; Rabelo, C. H. S. [UNESP]; Berchielli, Telma Teresinha [UNESP]; Teixeira, I. A. M. A. [UNESP]; Siqueira, G. R.; Reis, R. A. [UNESP] (Amer Soc Animal Science, 2014)
This study aimed to examine the effects of feeding corn silage inoculated without or with either Lactobacillus buchneri (LB) alone or a combination of LB and Lactobacillus plantarum (LBLP) on the apparent digestibility, ruminal fermentation, microbial protein synthesis, and growth performance of lambs. Thirty Santa Ines x Dorper crossbred intact males lambs weighing 20.4 +/- 3.8 kg were blocked by weight into 10 groups. Lambs in each group were randomly assigned to 1 of the following 3 dietary treatments: untreated (Control), LB, and LBLP silage. Lambs were fed experimental diets for 61 d. The apparent digestibility was indirectly estimated from indigestible NDF measured on d 57 to 59. Spot urine samples were collected from all animals on d 59 to estimate microbial protein synthesis. Lambs were slaughtered for carcass evaluation on d 61 when they weighed 32.4 +/- 5.2 kg. Six additional ruminally cannulated Santa Ines x Dorper crossbred wethers weighing 40.5 +/- 1.8 kg were used to examine dietary effects on ruminal fermentation. Average daily gain was increased when lambs were fed LBLP silage (P < 0.05) but not LB silage. The LBLP silage had the highest (P < 0.05) lactic acid concentration and both inoculated silages had greater acetic acid concentrations than the Control silage (P < 0.05). Inoculation of corn silage increased intakes of DM, OM, CP, NDF, total carbohydrate (CHO), and GE by the lambs but decreased digestibility of DM, OM, CP, total and nonstructural carbohydrates, and concentration of GE and ME. (P < 0.05). Nevertheless, lambs fed inoculated silages had greater microbial N supply than those on the Control treatment (P < 0.05). The acetate to propionate ratio was lower in ruminal fluid of wethers in LBLP treatment than LB and Control treatment (P < 0.05) and ruminal pH tended to be greater in LB lambs than in LBLP and Control wethers (P < 0.10). Finally, the inoculation with both bacteria combined enhanced the silage fermentation. The intakes of DM, OM, CP, NDF, and GE were improved in the lambs fed corn silage inoculated with L. buchneri alone or combined with L. plantarum. The microbial N supply was enhanced in the lambs fed corn silage inoculated with L. buchneri. The inoculation of L. buchneri combined with L. plantarum reduced the acetate to propionate ratio in ruminal fluid and improved the ADG of lambs.
Keywords: corn silage; digestibility; growth performance; heterofermentative inoculants; sheep